2013
DOI: 10.4161/isl.24029
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of PAK1 enhances Ubiquitin-mediated Survivin degradation in pancreatic β-cells

Abstract: Functional β-cell mass deficiency in diabetes results from imbalanced β-cell death and replication, and decreased PAK1 protein levels in human islets from donors with type 2 diabetes implicates a possible role for PAK1 in maintaining β-cell mass. Here, we aim to address the linkage between PAK1 and Survivin, a protein essential for β-cell replication. PAK1 knockout (KO) mouse islets exhibited decreased expression of Survivin protein. MIN6 β-cells with siRNA-mediated suppression of PAK1 also had decreased Survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…Increasing evidence has indicated that the ubiquitinproteasome system participates in the regulation of insulin signaling (26)(27)(28), and there have been several studies published on the transcriptional and post-transcriptional regulation of this system in the nucleolus (29)(30)(31). In our study, the results from immunohistochemistry revealed that the overexpression of ubiquitin in the hepatic nucleolus significantly correlated with the onset of insulin resistance and type 2 diabetes, when comparing the DG and IG mice with the CG mice.…”
Section: Discussionsupporting
confidence: 60%
“…Increasing evidence has indicated that the ubiquitinproteasome system participates in the regulation of insulin signaling (26)(27)(28), and there have been several studies published on the transcriptional and post-transcriptional regulation of this system in the nucleolus (29)(30)(31). In our study, the results from immunohistochemistry revealed that the overexpression of ubiquitin in the hepatic nucleolus significantly correlated with the onset of insulin resistance and type 2 diabetes, when comparing the DG and IG mice with the CG mice.…”
Section: Discussionsupporting
confidence: 60%
“…Since survivin is highly expressed in malignant cells, but not in normal cells, survivin could be a selective target for anti-cancer drugs. Interestingly, in 2013 a group at Indiana University found that PAK1-deficiency in mice inactivates survivin gene [51], clearly indicating that PAK1 is essential for transcription of survivin gene. Furthermore, we found that PAK1-deficient mutant of nematode (RB689) lives 60% longer than the wild-type [5], strongly suggesting the possibility that YM-155 could also extend the …”
Section: Ym155mentioning
confidence: 99%
“…First of all, these in ovo observations altogether have proven that both 15K and YM155 exert their potent anti-angiogenic activity by blocking their common oncogenic/angiogenic PAK1-survivin signaling pathway, as PAK1 is essential for survivin expression (10), and the potent survivin-suppressor YM155 indeed blocks PAK1 as well as AKT in cancer cells (9,11). To the best of our knowledge, both 15K and YM155 are the most potent anti-angiogenic PAK1-blockers so far.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a great surprise because it has been known that PAK1-deficient mice express far less survivin, clearly indicating that PAK1 is essential for survivin expression (10). Interestingly, however, YM155 blocks AKT by inhibiting epithelial growth factor (EGF) receptor (11).…”
mentioning
confidence: 96%